EFEK MEDIASI PROFITABILITAS PADA PENGARUH LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Debi Eka Putri; Rico Nur Ilham; Anggraini Syahputri (ITB AAS INDONESIA Surakarta, 2021)
The purpose of this study if determine the effect of leverage and firm size on firm value with profitability asintervening variable. The population in this study are Jakarta Islamic Index (JII) listed on the Indonesia Stock Exchange in the 2015-2019 period using a purposive sampling method, 14 companies were selected in the sample. Analysis of the data path analysis and sobel test which is assisted with SPSS 21 software. Based on the result of testing the data determine that leverage and firm size have a significant effect on profitability. Leverage and profitability have a significant effect on firm value but, firm size have not significant effect on firm value. Profitabilit not to be able to mediate the effect of leverage and firm size on firm value. Keyword : Leverage, Firm Size, Firm Value, Profitability